2021
DOI: 10.3390/polym13152446
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Circular Economy Material Using Fish Scales as a Natural Flame Retardant and the Properties of Its Composite Materials

Abstract: Fish scales (FSs) are fishery wastes that can cause environmental pollution. This study aimed to solve this environmental problem. FSs were used as a flame retardant for polymer materials, making them valuable. Fish scales were combined with a commercial flame retardant, ammonium polyphosphate (APP), through synergistic effects to reduce the amount of commercial flame retardant. The use of FSs conforms to the concept of a circular economy and lowers costs by reducing the consumption of APP. Thermogravimetric a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…For instance, when the addition amount of A‐E was 9.1 wt%, T 5 , T 10 , and T max got their minimum values, which dropped from 371.2 to 316.4°C, from 380.5 to 330.1°C and from 395.6 to 360.3°C, respectively. The reason behind this observation is related to the presence of P element in the A‐E filler, which triggered the pyrolysis of E‐D/A‐E composite at lower temperature 39 . In addition, the Y c for E‐D/A‐E 5 is about 30.46% which is 11.57% higher than that of the E‐D/A‐E 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, when the addition amount of A‐E was 9.1 wt%, T 5 , T 10 , and T max got their minimum values, which dropped from 371.2 to 316.4°C, from 380.5 to 330.1°C and from 395.6 to 360.3°C, respectively. The reason behind this observation is related to the presence of P element in the A‐E filler, which triggered the pyrolysis of E‐D/A‐E composite at lower temperature 39 . In addition, the Y c for E‐D/A‐E 5 is about 30.46% which is 11.57% higher than that of the E‐D/A‐E 1.…”
Section: Resultsmentioning
confidence: 99%
“…The next stage (about 360 ~ 395°C) was primarily related to the pyrolysis of E51 and DGED resins. The final stage was the dehydration of PPE near 450°C to obtain P 2 O 5 , and so forth 39,42 . In addition, the V max for all the E‐D/A‐E composites are lower than those of the neat resin revealing that A‐E flame retardants postpone the thermal decomposition of materials at higher temperature 43 …”
Section: Resultsmentioning
confidence: 99%
“…FSs can enhance the fire resistance of composites as a synergistic agent. By adding FSs to APP, Liu et al [90] found that the LOI went from 21.2% to 36.2% and the UL-94 test went from fail to V-0 rate. This indicated that the composite was less likely to catch fire at high temperatures.…”
Section: Waste Cooking Oil (Wco)mentioning
confidence: 99%